Pengaruh Variasi Suhu dan Waktu Penyimpanan Terhadap Karakteristik Nira Aren - Sinaga, Yesica Marcelina Romauli; Widyastuti, Sri; Ma’wa, Miftahil; Ariyana, Mutia Devi; Yuniarto, Kurniawan; Fuadi, Mi'raj (Pro Food, 2025)
Palm sap is one of the non-timber forest products (NTFPs) that has high economic potential as a raw material for palm sugar. However, the quality of palm sap is greatly influenced by storage conditions prior to processing. This study aims to determine the effect of temperature and storage duration on the microbiological, chemical, and physical characteristics of palm sap. Samples of palm sap were collected from Kekait Village, West Lombok, and stored at room temperature and cold temperature (4°C) for 3 to 24 hours. The parameters observed included total yeast, reducing sugar content, alcohol content, total acid titratable (TAT), and turbidity. Data were analyzed using two-way ANOVA, and post-hoc tests were conducted using the Honest Significant Difference at a 5% significance level. The results showed that temperature significantly affected alcohol content and turbidity of the sap. Meanwhile, time significantly affected reducing sugar content, alcohol content, TAT, and turbidity. The interaction between temperature and time significantly affected reducing sugar content, turbidity, and alcohol content. After 3 hours of storage, nira stored at cold temperatures and room temperature already showed a total yeast population of approximately 8 Log CFU/mL. Cold temperatures were not sufficiently effective in preventing yeast growth and nira degradation, as indicated by the production of fermentation products such as reducing sugars, acids, and alcohol.